First report of Lemmermanniella uliginosa (Synechococcaceae, Cyanobacteria) in South America, and the first record of the genus from Peru - Mendoza Carbajal, Leonardo Humberto (2020)
This work presents the first record of Lemmermmanniella uliginosa from Peru based on periphyton and sediment samples from Caucato wetland (San Clemente district, Ica department). Furthermore, the genus Lemmermmanniella is recorded for the first time for Peru. Morpho-taxonomic comparison with other populations reported in tropical regions is discussed.